Comparative evaluation of colposcopy, cytology and histopathology for diagnosis of cervical lesions - Saxena, Rashmi; Agrawal, Alpana; Agarwal, Neelima; Gupta, Manisha; Shubham, Divya; Rathore, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cervical cancer is the fourth most frequent cancer globally in women with an estimated 570,000 new cases and 311,000 deaths in 2018 representing 6.6% of all female cancers. To correlate the cytology, colposcopy and histopathology of cervical lesions in patients attending gynaecology OPD in a tertiary care centre, Ghaziabad. Methods: 208 women were enrolled from Gynaecology OPD of Santosh Medical College and Hospital, Ghaziabad, irrespective of their chief complaints. Women aged 19-80 years were included in the study group. Those with pregnancy and already diagnosed or treated with CIN, Cervical cancer or Cervical HPV infection were excluded from the study. PAP-smear was taken for all the patients followed by colposcopy without waiting for PAP-smear report. Cervical biopsy was taken from patients with abnormal colposcopic findings (90 patients). Results: Majority of women were in age group 30-39 years. 37.5% had unhealthy, 21.6% had hypertrophied cervix and only 9.1% had normal cervix. It was found that PAP -smear has a sensitivity of 33.33%, specificity of 92.59%, accuracy of 68.89%, positive predictive value of 75% and negative predictive value of 67.57%. Test parameters calculated for colposcopy revealed that it has sensitivity of 73.33%, specificity of 92%, PPV of 64.7%, NPV of 94.52% and accuracy of 88.89%. Conclusions: The results from the current study conclude that it is better to use cytology and colposcopy together as part of routine screening for cervical cancer rather than pap smear alone in order to detect maximum number of lesions.